Shareholder Activism and Firm Performance: A Review - Simon Rafaqat; Sana Rafaqat; Sahil Rafaqat; Saoul Rafaqat; Dawood Rafaqat (Journal of Economics and Behavioral Studies, 2023)
The paper aims to review the literature on the influence of Shareholder Activism on firm performance including share price, financial performance, corporate governance, and innovation. Many studies have been reviewed to find the relationship between the identified constructs. For this purpose, the review methodology has been used to go through the literature relating to the impact of Shareholder Activism on Firm Performance over the period ranging from 2000 to 2021. Furthermore, the study concludes that shareholder activism significantly affects how well a company performs. However, studies claim that shareholder activism has a favorable impact on a company's performance, while other scholars claim that it has a detrimental effect. However, some researchers have found that the influence is minimal. Moreover, firm performance can be enhanced if a firm's management works in collaboration with activist investors.